Pemberdayaan Siswa Yatim Sekolah Tahfidz Muamalah Al Qudsiyah Melalui Pengembangan Pengolahan Ikan Nila dan Pemasaran Prosuk Berbasis E-Commerce - Mustarin, Amirah; Indrayani; Rahma Jabir, Sitti; Dwi Anggraini, Annisa; Hidayat, Taufik (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
PKM empowerment of orphan students of Tahfidz Muamalah Al Qudsiyah school through the development of tilapia processing and marketing of e-commerce-based products is a new technology and innovation implemented to answer the problem of food needs and independence through school business units. The partners involved are all students of Tahfidz Muamalah Al Qudsiyah school. The technology introduced to partners is frozen tilapia ready for consumption and marketing through online media. This fresh tilapia is processed with yellow spices that are rich in spices, giving it a delicious and authentic taste. The product is packaged using vacuum sealing techniques to maintain its freshness, quality, and hygiene. Once packaged, the fish is frozen at -18°C to ensure a longer shelf life without compromising on flavor or nutrition. Marketing is done digitally, reaching a wider target market efficiently. This PKM is carried out in 5 stages, namely the socialization stage, the training stage, the technology application stage by providing fish processing facilities as a learning medium for students, mentoring and evaluation, and program sustainability. From this PKM activity, fish processing and marketing facilities have been provided, and continue to support the sustainability of tilapia cultivation production with the biofloc system. The results of the implementation of PKM activities are known to have increased the level of partner empowerment from the production aspect by 72% and the marketing aspect by 67%. The conclusion of the implementation of PKM activities, namely tilapia processing development training has been completed with partners by producing processed yellow spice tilapia and e-commerce-based product marketing training has been completed with partners with the participation of partners who are very enthusiastic about marketing products produced through e-commerce. And through this activity, a brand or brand was obtained for processed tilapia products produced by partners, namely Tilapia Fresh Freeze.